Economic Vulnerability of Cereal Production in Northern Algeria under Climate Change: Cost-Benefit Analysis of Adaptation Strategies Using DSSAT-SWOT - ARIBI Mohamed, MAROUF (Research on World Agricultural Economy, 2025)
This study examines the economic vulnerability of cereal production to climate change across four key regions of northern Algeria, Blida, Tizi Ouzou, Tiaret, and Sétif, selected for their agro-climatic diversity and strategic contribution to national grain supply. By integrating DSSAT crop modeling with a SWOT-AHP multi-criteria framework, the research evaluates adaptation strategies through a cost-benefit perspective. Climate projections under RCP4.5 and RCP8.5 (2025–2050) suggest potential cereal yield declines of 18% to 40% by mid-century, which could raise annual cereal import costs by 1.2 billion and result in the loss of up to 12,000 agricultural jobs. Among the climatic constraints, heat stress during the flowering stage emerges as the most critical yield-limiting factor. Stakeholder-weighted prioritization highlights drip irrigation (BCR = 2.8) and drought-tolerant seed varieties (BCR = 1.9) as the most economically viable interventions, though both require substantial initial investment (≈ 500 million) and subsidy reforms. The findings reveal significant trade-offs within Algeria’s agricultural policy but underscore that reallocating existing cereal subsidies toward climate-smart technologies could considerably strengthen resilience while maintaining food security in semi-arid regions. Beyond Algeria, the study provides a replicable framework for other countries facing similar climate–agriculture challenges, combining biophysical modeling with participatory decision-making to guide cost-effective adaptation.